Impact of Australia's No Jab, No Pay policy on vaccination uptake – a before-after study in two national birth cohorts - Beard, Frank; Hendry, Alexandra J.; Gidding, Heather F.; Dey, Aditi; Macartney, Kristine; Leask, Julie; McIntyre, Peter (The Lancet regional health. Western Pacific)
Data on impact of financial penalties for non-vaccination are sparse. Australia has required full vaccination for government family assistance payment eligibility since 1998. In 2016, the No Jab, No Pay (NJNP) policy removed registered non-medical objection as exemption option and increased eligibility assessment to yearly. We aimed to examine NJNP impact on vaccine uptake in children. Individual-level Australian Immunisation Register data were used to assemble two-year-wide pre-/post-NJNP birth cohorts aged 1–